Clinico-epidemiological profile of childhood cutaneous tuberculosis - Sanju Babu Shrestha; G P Pokhrel; S B Pradhan (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Although cutaneous tuberculosis constitutes a small percentage of extra pulmonary tuberculosis, it has not been fully documented in Nepal and more so in the pediatric population.